معادلات دیفرانسیل مرتبه اول درجه یک کامل

داریم
                                                    M = ax+by+f  -->  M'y = b

و
                                                   N = bx+hy+e  -->  N'x = b

بنابراین معادله کامل بوده و برای حل آن داریم

                                        c$ (ax+by+f).dx + $ (hy+e).dy = c

و یا
                                       ax2/2 + byx + fx + hy2/2 + ey = c

امتحان جواب به دست آمده :

                                             f'x = ax+by+f  ;  f'y = hy+bx+e

و
                                                 (y' = - (ax+by+f)/(bx+hy+e

/ 0 نظر / 12 بازدید